Zirconium-Based Metal–Organic Frameworks for the Catalytic Hydrolysis of Organophosphorus Nerve Agents - Kirlikovali, Kent O; Chen, Zhijie; Islamoglu, Timur; Hupp, Joseph T; Farha, Omar K (ACS applied materials & interfaces, 2020)
Organophoshorus nerve agents are among the most toxic chemicals known to humans, and because of their unfortunate recent use despite international bans, there is an urgent need to develop materials that can effectively degrade these nerve agents. Within the past decade, zirconium-based metal–organic frameworks (Zr-MOFs) have emerged as a bioinspired class of materials capable of rapidly hydrolyzing these compounds and significantly diminishing their toxicity. Both experimental and computational insights have guided the design of Zr-MOFs, leading to the development of catalysts capable of detoxifying nerve agents and simulants, chemicals with similar functionality but lower toxicity, via hydrolysis within seconds in basic aqueous solutions. While these systems are acceptable for the elimination of stockpile weapons, translating this catalytic performance to filters incorporating Zr-MOFs that can be used in masks or protective clothing is not trivial. As such, a large area of focus recently has been targeted toward integrating these hydrolysis catalysts into protective clothing and gear while retaining the performance from solution-based catalytic systems. This Forum Article provides an overview of the development of Zr-MOFs for the catalytic hydrolysis of organophosphorus substrates, including design principles and mechanistic insights for both solution-based and textile-coated systems. Finally, we highlight the remaining challenges yet to be addressed and offer perspectives on the future directions for this field.